2011
DOI: 10.1007/s00335-011-9324-8
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in Fgfr1 causes ear and skull defects in hush puppy mice

Abstract: The hush puppy mouse mutant has been shown previously to have skull and outer, middle, and inner ear defects, and an increase in hearing threshold. The fibroblast growth factor receptor 1 (Fgfr1) gene is located in the region of chromosome 8 containing the mutation. Sequencing of the gene in hush puppy heterozygotes revealed a missense mutation in the kinase domain of the protein (W691R). Homozygotes were found to die during development, at approximately embryonic day 8.5, and displayed a phenotype similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…Fgfr1 mutant mice have abnormal stapes anatomy, increased compound action potentials and skeletal defects (Calvert et al, 2011). Fgfr1 expression is decreased in Chd7 mutant olfactory placodes (Layman et al, 2011), and may also have roles in inner and middle ear development.…”
Section: Discussionmentioning
confidence: 99%
“…Fgfr1 mutant mice have abnormal stapes anatomy, increased compound action potentials and skeletal defects (Calvert et al, 2011). Fgfr1 expression is decreased in Chd7 mutant olfactory placodes (Layman et al, 2011), and may also have roles in inner and middle ear development.…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenotype is dependent on genetic background, since Fgfr1 was shown to regulate primitive endoderm formation on a 129S4 genetic background, while the same null allele caused mesoderm defects on a mixed genetic background (Hoch and Soriano 2006;Brewer et al 2015). Other studies have also demonstrated that ear defects caused by an ENU-induced mutation in Fgfr1 are also modified by genetic background (Pau et al 2005;Calvert et al 2011). For Fgfr2, different targeting strategies have produced distinct phenotypes.…”
Section: Fgfrs Function Individually and In Combinationmentioning
confidence: 99%
“…Fgfr1-related phenotypes are subject to variation depending on the genetic background (Hoch and Soriano 2006;Calvert et al 2011). To minimize phenotypic variability, we analyzed mouse mutants on 129S4 coisogenic or congenic genetic backgrounds.…”
Section: Fgfr1 Contributes To Primitive Endoderm Formationmentioning
confidence: 99%
“…−/− studies due to differences in genetic backgrounds, which have been shown to influence Fgfr1-associated phenotypes (Calvert et al 2011).…”
Section: Fgfr1mentioning
confidence: 99%